Obtaining Probabilistic Characteristics of Electrical Quantities and their Imbalances; EEA - Electrotehnica, Electronica, Automatica; Vol. 67, iss. 3 - Bay Yu. D. Yuly Dmitrievich; Razzhivin I. A. Igor Andreevich; Kievets A. V. Anton Vladimirovich; Askarov A. B. Alisher Bakhramzhonovich; Rudnik V. E. Vladimir Evgenevich (2019, 2019)
Title screen